General self-assembly of metal/metal chalcogenide heterostructures initiated by a surface linker: modulating tunable charge flow toward versatile photoredox catalysis. Issue 37 (4th September 2019) - Li, Tao; Huang, Ming-Hui; Li, Yu-Bing; Dai, Xiao-Cheng; He, Yunhui; Xiao, Guangcan; Xiao, Fang-Xing
Abstract : Interfacial charge transfer over metal/metal chalcogenide heterostructures was finely tuned by a facile, green, scalable, and simple yet efficient surface ligand-triggered self-assembly strategy for multifarious photoredox catalysis. Abstract : Interfacial charge separation and transfer enduringly constitutes a core issue, which dictates the efficiency of a photocatalytic reaction. However, the exquisite modulation of directional charge transfer to ideal reaction sites remains challenging in terms of the fast recombination rates of photoinduced charge carriers and the difficulty in constructing spatially separated high-speed charge transfer channels. Herein, we demonstrate the general construction of metal/metal chalcogenide heterostructures by a facile, green, universal, scalable and simple yet efficient electrostatic self-assembly strategy, wherein tailor-made positively charged 4-dimethylaminopyridine (DMAP)-capped metal nanocrystals (NCs, Au, Pd) were spontaneously and intimately tethered on negatively charged one-dimensional (1D) transition metal chalcogenides (TMC: CdS, CdIn2 S4, ZnIn2 S4, and Zn0.5 Cd0.5 S) initiated by a surface linker (DMAP) to fabricate well-defined heterostructured photocatalysts. Moreover, the interface configurations between the metal NCs and TMC matrices were finely designed by ligand engineering to afford controllable charge transfer pathways. Intriguingly, this tunable charge flow endows the metal NC/TMC heterostructures with markedly enhanced and versatile photoredox performance toward the anaerobic-selective photoreduction of aromatic nitro compounds, photocatalytic hydrogen generation, and photocatalytic selective oxidation of aromatic alcohols under visible light irradiation, in which metal NCs play imperative roles in efficiently capturing Schottky-junction-driven electrons from the TMC substrates without the interference of the hierarchically branched ligand capped on the metal NCs. Our studysheds light on the rational modulation of interfacial charge flow in photoredox catalysis for substantial solar energy conversion.